A God So Near Essays on Old Testament Theology in Honor of Patrick D. Miller - Bowen, Nancy R.; Bowen, Nancy R.; Brueggemann, Walter; Cross, Frank Moore; Hossfeld, Frank-Lothar; Janzen, J. Gerald; Lemke, Werner E.; Limburg, James; Lohfink, Norbert; Mays, James Luther; Nelson, Richard D.; Olson, Dennis T.; et al. (Penn State University Press, 2021)
Patrick Miller is widely known as an educator, editor, President of the Society of Biblical Literature, and academic who is concerned to ensure that academics and the life of the church are not torn asunder in this era of fragmentation. As the editors note, "The depths of Miller's contributions to church and academy are reflected in the depth of his relationships with family, friends, and colleagues." This volume honors him for his life's work, presenting 24 essays by students and colleagues on themes dear to Miller: (1) the Psalms and God's nearness to his people, and (2) Torah (Deuteronomy, in particular) and God's connection with his people in their lives together. A bibliography of Miller's writings is also included